PENGARUH ANEMIA DAN STATUS GIZI TERHADAP KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI RSUD Dr. M. YUNUS BENGKULU TAHUN 2016 - Suzanna Fabella Putri (STIKes IMC Bintaro, 2017)
Babies with low birth weight ( LBW ) is one health problem in Indonesia, which could result in higher infant mortality rate and as an indicator of the low level of public health and have a contribution to infant mortality, especially in the perinatal period. LBW causative factor generally consist of three , namely : maternal factors , fetal and environment. The biggest contributor to the incidence of LBW in hospitals Dr. M. Yunus Bengkulu is anemia and nutritional status. This study aims to identify and explain the effects of anemia and nutritionl status with the low birth weight incidence in Dr. M. Yunus Bengkulu Hospital. This research is a quantitative research with Case Control design. This study was conducted in April-May 2016. The population in this study were all women who giving birth in Dr. M. Yunus Bengkulu hospitals many as 746 people . The case population was 286 and control population was 460. The case and control sample was 166 (1:1). Case taken by using systematic random sampling. Analysis using univariate, bivariate analysis using chi -square and multivariate analysis using multiple logistic regression. The results obtained by analysis were anemia, nutritional status,birth interval, occupation and parity has a significant effect with LBW while variable maternal age and gender of the baby is obtained not associated with LBW . Anemia is a dominant factor influenced the incident of low birth weight with p value = 0.000 and OR = 7.692 after controlled nutritional status, birth interval, and parity. It is advisable to do a counseling and monitoring of pregnant women about the importance of iron tablet consumption for a healthy fetal growth and prevent of anemia .